A mutiny in time - Dashner, James,, 1972- (New York, N.Y.: Scholastic Inc., 2012)
Time has gone wrong, and best friends Dak Smyth and Sera Froste, together with the young Hystorian Riq, must use the infinity ring to travel back to one of the Great Breaks--a mutiny on the Santa Mari?a--to correct history and defeat the SQ.
Keywords: World history; Time travel; World history; Conspiracies; Best friends; Friendship; Science fiction; Time travel; Conspiracies; Best friends; Science fiction